Community Composition of Photosynthetic Picoeukaryotes in a Subtropical Coastal Ecosystem, with Particular Emphasis on Micromonas. (13th October 2016) - Lin, Yun‐Chi; Chung, Chih‐Ching; Chen, Liang‐Yin; Gong, Gwo‐Ching; Huang, Chin‐Yi; Chiang, Kuo‐Ping
Abstract: Photosynthetic picoeukaryotes (PPEs) are important constituents in picoplankton communities in many marine ecosystems. However, little is known about their community composition in the subtropical coastal waters of the Northwestern Pacific Ocean. In order to study their taxonomic composition, this study constructed 18S rRNA gene libraries using flow cytometric sorting during the warm season. The results show that, after diatoms, prasinophyte clones are numerically dominant. Within prasinophytes, Micromonas produced the most common sequences, and included clades II, III, IV, and VI. We are establishing the new Micromonas clade VI based on our phylogenetic analysis. Sequences of this clade have previously been retrieved from the South China Sea and Red Sea, indicating a worldwide distribution, but this is the first study to detect clade VI in the coastal waters of Taiwan. The TSA‐FISH results indicated that Micromonas clade VI peaked in the summer ( 4 × 10 2 cells/ml), accounting for one‐fifth of Micromonas abundance on average. Overall, Micromonas contributed half of Mamiellophyceae abundance, while Mamiellophyceae contributed 40% of PPE abundance. This study demonstrates the importance of Micromonas within the Mamiellophyceae in a subtropical coastal ecosystem.